Analysis of the Influence of Social Media Content, Influencer Marketing, and Customer Reviews on Purchase Decisions in TikTok Shop - Kristina, Erin; Realize, Realize (Dinasti Publisher, 2025)
Abstract: This study aims to analyze the influence of social media content, influencer marketing, and customer reviews on purchasing decisions on TikTok Shop, as well as the factor underlying the increase in user transactions on TikTok Shop. This phenomenon is relevant given the high intensity of social media use as a means of promotion and consumer decision-making in the digital era. The study uses a quantitative approach with a survey method by distributing Likert-scale questionnaires to 150 respondents who are active TikTok Shop users in Batam City. Data testing was conducted through validity and reliability tests, classical assumption tests, and multiple linear regression analysis to measure both the simultaneous and partial effects of each independent variable on the dependent variable. The results of the analysis show that all three independent variables have a significant effect on purchasing decisions. Simultaneously, these three variables contribute 57.2% in influencing purchasing decisions. In the digital era, consumers no longer rely on a single source of information, but instead integrate various sources from content and testimonials to public figure opinions to make purchasing decisions. The increase in TikTok Shop usage, reflected in its high Gross Merchandise Value (GMV), can be explained by the significant roles of Social Media Content, Influencer Marketing, and Customer Reviews. These three factors have proven to be important drivers influencing users’ purchasing decisions on the platform. User behavior tendencies that differ by region are also acknowledged as contextual factors that may affect the study's results. Therefore, these findings can serve as a reference for businesses to adjust their digital marketing strategies on TikTok Shop. This study contributes by encouraging TikTok Shop sellers or users to develop creative, informative, and relevant content. Business actors can also collaborate with influencers whose image aligns with their brand and who have strong relationships with their followers. Encouraging customers to provide honest reviews can increase both the quantity and quality of testimonials.